Irrigation Water Supply Optimization Model in Jurang Batu Irrigation Area, Central Lombok District - Putri, Ni Komang Triya Apriani Paramitha; Setiawan, Ery; Pracoyo, Atas (International Journal Labs, 2025)
The Jurang Batu Irrigation Area is an irrigation area located in Central Lombok Regency. The Jurang Batu Irrigation Area is one of the service areas of the Jangkok-Babak High Level Diversion (HLD) Canal. The HLD canal is an interconnection channel between watersheds on Lombok Island, its purpose is to supply excess water from the Jangkok watershed to the southern Lombok irrigation area. The uneven water allocation conditions in the HLD system cause downstream areas to often experience water crises, so the construction of the Meninting Dam is expected to be able to increase the supply of discharge to the South Lombok region. The Meninting Dam will later replace the irrigation discharge in part of the Sesaot Irrigation Area area so that by replacing some of the water in the Sesaot Irrigation Area, it is expected that the Jangkok - Babak HLD supplementary discharge can be increased. From the analysis results, it is known that the average discharge obtained by the Jurang Batu Irrigation Area from the additional water allocation after the construction of the Meninting Dam is 69.15 lt / second, and after optimization, alternative II, namely with AMT December II, is the most optimal alternative, with the acquisition of agricultural profits of Rp. 88,152,598,737.74 (eighty eight billion one hundred fifty two million five hundred ninety eight thousand seven hundred thirty seven point seventy four rupiah).